2020
DOI: 10.1111/1365-2435.13648
|View full text |Cite
|
Sign up to set email alerts
|

What are you actually measuring? A review of techniques that integrate the stress response on distinct time‐scales

Abstract: 1. The field of stress physiology has rapidly expanded, particularly in those fields interested in identifying chronic stress in wild animals. Despite this expansion, stress remains difficult to assess and understand, due in large part to the temporal complexities of common stress measurement techniques. 2. While the stress response happens on a short timescale , chronic stress results over longer timescales. Therefore, the temporal dynamics of techniques used to assess 'stress' need to be fully understood in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 139 publications
1
99
0
Order By: Relevance
“…Second, we found that these three physiological parameters showed different kinetic dynamics over the time course of the short-term stress response, reflecting different response latencies (Fig. 2) (Gormally and Romero, 2020). CORT levels increased markedly in most individuals, but the timing of the peak response underlies substantial between-individuals variation (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Second, we found that these three physiological parameters showed different kinetic dynamics over the time course of the short-term stress response, reflecting different response latencies (Fig. 2) (Gormally and Romero, 2020). CORT levels increased markedly in most individuals, but the timing of the peak response underlies substantial between-individuals variation (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…This relationship was previously demonstrated in CORT supplementation experiments, but also capture and restraint stress was shown to be sufficient to effect similar responses as is corroborated by a growing number of studies on vertebrates (Cīrule et al, 2012; Davis et al, 2008; Lentfer et al, 2015). The H:L ratio, however, is considered to mainly reflect long-term, rather than an immediate, short-term physiological stress response (Gormally and Romero, 2020; Maxwell, 1993; O’Dell et al, 2014) and there is a strong indication that an increase after capture becomes significant only 30 to 60 min post-capture and in a species-specific manner (Davis, 2005; Davis and Maney, 2018). Remarkably, our data show an unexpectedly fast decrease in the H:L ratio at 15 min after capture, followed by rapid recovery to baseline levels 30 min post-capture.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations